Implementation of Finite State Automata on e-Knows Telegram Chatbot - Alam, Cecep Nurul; Firdaus, Imam (CoreID Journal, 2023)
The State Islamic University of Sunan Gunung Djati Bandung has a bold learning system called e-Knows. So far, if the user has a school, he must contact the admin manually. The problems are diverse, and several issues can bring personal impact. Automata language theory is the basic logic for mapping the telegram e-Knows chatbot system. The mapping is done by dividing each system using finite state automata to facilitate the completion of the system.